THE USE OF KNOW, WANT TO KNOW AND LEARNT (KWL) STRATEGY TO IMPROVE READING COMPREHENSION - Ummul Khaira (Universitas Syiah Kuala, 2015)
This Classroom Action Research (CAR) was conducted to find out how KWL strategy is applied in English reading class and the students’ responses towards it. It was done in 2 cycles, in which each cycle consisted of planning the action, implementing the action, observing the action, and reflection. The instruments used in collecting the data were tests, observation sheets for the researcher and students, and questionnaires for the students. The results showed that KWL strategy gave better result in improving the students’ reading comprehension skills in finding out the main idea, detailed information, word meaning, and references. The results from tests showed that students’ mean score from pre-test was 62.8 and this increased to 68.2 at the end of cycle 1, and reached 80.4 at the end of cycle 2. Furthermore, the percentage of students’ participation in the teaching and learning process gradually increased. This is shown from the observation checklist where the percentage of students’ involvement is 57% (in the enough category) in cycle 1 and increased up to 80% (in the very good category) in cycle 2. It means that they worked well in conducting all activities. Furthermore, the results of questionnaire showed that 80% of the students responded positively towards the implementation of KWL. This strategy was found to help overcome problems encountered by teachers in getting the students to be more active to participate in the process of learning, expanding knowledge, learning about their needs and their interests, and activating their background knowledge.